The Mediating Effect of Representativeness Heuristic on Neurofinance and SME’s Financial Decision Making - Ismail, Nurazleena; Nik Muhammad, Nik Maheran; Wan Husin, Wan Zakiyatussariroh; Ab Halim, Aini Ismafairus (International Journal of Criminology and Sociology, 2022)
Financial decision-making is a crucial part of business survival, especially among SMEs. About 95% of the business are facing failures within five-year time. The financial decision making failure happened due to psychology and behavioural. This research aims to determine the mediating effect of representativeness heuristic on emotions and financial decision making. A pre-test and post-test experiment analyzes emotions, financial decision-making, and representativeness heuristic behaviour. In pre-testing, emotions and financial decision-making questionnaires are measured using questionnaires distributed to forty-two SMEs. Then, the video clips with 12 to 16 minutes duration are used in manipulating the emotions from neutral emotion to positive and negative emotions. Lastly, in post-testing, the data are gathered by repeating answered emotion and financial decision-making questionnaires, followed by the representativeness heuristic questionnaire. The data were analysed using General Linear Regression. The results showed that representativeness heuristic is partially effect on negative emotion towards financial decision making. From the analysis, neuro-behavioural of financial decision-making model has been proposed. The proposed models are incorporating with the brain components and working memory. It shows that System 1 and System 2 of the dual-process theory are activated for negative and positive emotions.